Unpacking the black box of trade credit to socially responsible customers - Zhang, Yanlei; García Lara, Juan Manuel; Tribó, Josep A. (Journal of Banking & Finance, 2020)
We investigate whether suppliers value customer firms’ socially responsible activities by examining the relation between corporate social responsibility (CSR) and firms’ access to trade credit. We posit that firms with better social performance are more likely to receive trade credit because suppliers view customers’ CSR activities as a signal of trustworthiness and of the capacity to meet financial obligations. In addition to this direct channel, we describe other channels: a) trade credit opens the possibility for suppliers to secure a share of their customers’ future business opportunities, which are expected to be higher for socially responsible firms, and b) the risk associated with the diffusion of negative shocks through the supply chain due to trade credit is lower for socially responsible firms, making them more attractive partners for suppliers. Consistent with our predictions, we find that socially responsible customers receive more trade credit from suppliers. This relation is more pronounced in situations where the aforementioned channels are more relevant: namely, when the financial health of a customer is of greater importance to its suppliers; when there are greater information asymmetries between suppliers and customers due to a lack of close transactional relationships; when socially responsible activities are more likely to generate growth; and when suppliers are exposed to higher risk in the customer-supplier relationship. We also document that during the global financial crisis, socially responsible customers offered backward liquidity provision to suppliers by reducing their use of trade credit, which represents an extra benefit of having socially responsible customers in production networks.